ANALISIS PENINGKATAN KUALITAS PRODUK GARAM PADA UD. H. SYAIFUL ULUM PANGARENGAN KABUPATEN SAMPANG DENGAN PENDEKATAN QUALITY RISK MANAGEMENT - Devi Lestari Pramita Putri (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2022)
UD. H. SYAIFUL ULUM Pangarengan is a company that manages or produces salt. Salt farming has become a source of income for the Madurese, especially in the village of Pangarengan. So the island of Madura dubbed the island of salt. In fact, nowadays the government prefers to import salt from neighboring countries rather than buying it from local salt farmers. The quality of salt products is one of the competitiveness for local farmers in order to compete in the world market. The method used in this research is qualitative research. The type of data used is qualitative data, the object of research is carried out at UD. H. SYAIFUL ULUM Pangarengan. Sources of data used are primary data and secondary data. This study uses data collection techniques in the form of observation, interviews and documentation. Variable operational definitions are product quality and Quality Risk Management. The data analysis technique used is to prepare data, identify, analyze and evaluate. Based on the results of the study, it was found that the process of producing salt from seawater is strongly influenced by the climate and weather of an area. The quality of the salt produced is influenced by various factors, namely temperature, climate, weather, water viscosity, soil, and geomembrane. The risk management owned by the company for the production of KW 1 salt is having competitiveness in the installation process. Meanwhile, the risk management owned by the company for the production of KW 3 salt is that the company experiences production costs that are greater than the profit earned.